A case of lupus erythematosus profundus with severe ulceration that responded to tumor necrosis factor-alpha–blocking agents - Daiki Nakagomi (Archives of Rheumatology, 2022)
A 61-year-old woman developed a malar rash, arthritis, and nephrotic syndrome 40 years ago. At that time, although renal biopsy was not performed, she was positive for anti- double-stranded deoxyribonucleic acid (anti- dsDNA) antibodies and anti-nuclear antibodies (ANA) and, therefore, she was eventually diagnosed with systemic lupus erythematosus (SLE). She was treated with 80 mg/day of prednisolone monotherapy. As SLE became less active, the dosage of prednisolone was tapered to 12.5 mg every other day. When the patient reached 59-year-old, she developed atrophic and scaly erythema on her lower legs, and she was clinically diagnosed with discoid lupus erythematosus (DLE). Two years later, scaly erythema eventually progressed to severe ulcerations (Figure 1a). Aside from these, there were no other significant physical findings. The patient did not have cytopenia or hypocomplementemia. C-reactive protein and urinalysis results were also normal. At this point, she was negative for ANA, anti-dsDNA antibodies, and any other antibody profiles, including anti-scleroderma-70 and anti-phospholipid antibodies. Based on a published article of lupus erythematosus profundus (LEP) in patients with DLE1 and the fact that this condition led to cutaneous atrophy and ulceration, a diagnosis of LEP with severe ulceration was made. Therefore, the patient received prednisolone at a dose of 40 mg/day and tacrolimus at a dose of 3 mg/day. However, the ulcers were refractory to treatment, despite treatment adherence for two months. Accordingly, we added etanercept at a dose of 50 mg/week. One week after the first subcutaneous injection of etanercept, ulcerations showed onset of granulation and epithelialization. After two months, ulcerations completely epithelialized leaving behind an atrophic scar (Figure 1b). At this point, we tapered the dose of prednisolone to 5 mg, while continuing etanercept. For almost two years now, the recurrence of LEP and DLE has not occurred. Moreover, the patient has no infections currently. A written informed consent was obtained from the patient for the publication of this case sreport. <f1> This is the first case of LEP with severe ulcerations that responded well to etanercept. Lupus erythematosus profundus occurs in 2 to 5% of patients with DLE or SLE. In addition, ulceration has been reported to occur in 6 to 28% of patients with LEP.[1,2] Recently, reports have shown that LEP-related ulcerations can be controlled with cyclosporine or tacrolimus.[3] However, this patient did not respond to tacrolimus. Regarding tumor necrosis factor-alpha (TNF-α) blockade, a report showed that LEP could be controlled with infliximab[4] and that TNF- α-blocking therapy was potentially useful in SLE treatment.[5] In SLE, keratinocytes are regarded as a major source of TNF-α.[6] High levels of TNF-α lead to the activation of B, T, and dendritic cells, promoting inflammation. Moreover, excessive TNF-α expression delays wound healing due to α-smooth muscle actin expression suppression.[7] The level of TNF-α is high in the serum and skin lesions of patients with SLE; hence, TNF-α blockade averts these mechanisms and explains the effectiveness of etanercept. In conclusion, TNF-α inhibitors are likely efficacious in patients with severe cutaneous lupus erythematosus.